Scenario planning in science‐centric organizations. Issue 2 (28th January 2020) - Ramirez, Rafael; McGinley, Ciaran; Rissanen, Jenni
Abstract: This paper surveys how, why, and with what effects organizations whose activity is centered on the work of the natural sciences and their application to societal issues, and whose core staff are natural scientists—often working with a positivist epistemology—use scenario planning. Based on three cases, we research how the scenario planning methodology was utilized, why it was selected, and with what effects. Our research suggests that scenario planning can be deployed to enhance the social engagement which science requires to operate; and which enables science and the organizations which support it to justify the value which science creates and thus to help secure its funding and restate and render explicit what the purpose of such organizations is. This paper contributes to scenario planning scholarship by extending the type of organizations which can benefit from deploying the methodology (we believe it is the first paper to explore how scenario planning is used by scientific organizations); and it also contributes to understanding how the construct of post‐normal science is enacted in practice. It does so by including in this practice a longer time horizon with which an extended peer community can assess scientific values.